Change management in the context of the Fourth Industrial Revolution: An exploratory research using qualitative methods (The Journal of Modern Project Management, 2022)
For manufacturing companies especially, the arrival of the 4th Industrial Revolution or Industry 4.0 has meant a leap forward and a considerable influx of innovation while new technologies are combined with increasing human knowledge and technological skills to automatize manufacturing processes and move towards a customized production culture. The aim of this exploratory research paper is to evaluate Industry 4.0 technology adoption and define the leading agents that contribute or hinder such an implementation in the scope of change management. The investigation of the adoption challenges will be made using two methodologies. Firstly, with a literature review and secondly with a statistical review using qualitative research methodologies of transcripts of readily available interviews with four Canadian manufacturers.